The Demise of Religion How Religions End, Die, or Dissipate - Stausberg, Michael; Cusack, Carole M.; Wright, Stuart A. (Bloomsbury Academic, 2020)
Why do religions fail or die? Taking a multidisciplinary approach, this open access book explores this important question that has received little scholarly attention to date. International contributors provide case studies from the United States, England, Sweden, Japan, New Guinea, and France resulting in a work that explores processes of attenuation, disintegration, transmutation, death, and extinction across cultures. These include: instances where mass suicides or homicides resulted in religious dissolution; the fall of Mars Hills Church and its larger-than-life megachurch pastor, accused of plagiarism and bullying in 2012; the death of the last member of the Panacea Society in England in 2012; and the disintegration of Knutby Filadelfia, a religious community in Sweden with Pentecostal roots that ceased to exist in May 2018 after a pastor shot his wife. Combining case studies and theoretical contributions, The Demise of Religion: How Religions End, Die, or Dissipate fills a gap in literature to date and paves the way for future research The eBook editions of this book are available open access under a CC BY-NC-ND 3.0 license on www.bloomsburycollections.com. Open access was funded by the Centre for Advanced Study at theNorwegian Academy of Science and Letters.